1993
DOI: 10.1126/science.7903479
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Activation Antigen, CD26, as a Cofactor for Entry of HIV in CD4 + Cells

Abstract: The CD4 molecule is essential for binding HIV particles, but is not sufficient for efficient viral entry and infection. The cofactor was shown to be dipeptidyl peptidase IV (DPP IV), also known as CD26. This serine protease cleaves its substrates at specific motifs; such motifs area also highly conserved in the V3 loops of HIV-1, HIV-2, and related simian isolates. Entry of HIV-1 or HIV-2 into T lymphoblastoid and monocytoid cell lines was inhibited by a specific monoclonal antibody against DPP IV or specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(110 citation statements)
references
References 68 publications
3
104
3
Order By: Relevance
“…By biochemical approaches, different cell surface proteins have been reported to interact with the V3 loop of gp120 (15)(16)(17)(18)(19)(20) and gp41 (21)(22)(23)(24); however, in most cases the relationship between the interaction and a putative role in HIV infection has not been determined. We have previously reported that CD26, through a potential interaction with the V3 loop, may serve as a cofactor of HIV entry (25)(26)(27). Using other experimental approaches, several groups initially were not able to produce similar results; their criticisms with our response have been published (28 -32).…”
Section: Table II the Higher Activity And Stability Of 5[k (Ch 2 N)prmentioning
confidence: 45%
“…By biochemical approaches, different cell surface proteins have been reported to interact with the V3 loop of gp120 (15)(16)(17)(18)(19)(20) and gp41 (21)(22)(23)(24); however, in most cases the relationship between the interaction and a putative role in HIV infection has not been determined. We have previously reported that CD26, through a potential interaction with the V3 loop, may serve as a cofactor of HIV entry (25)(26)(27). Using other experimental approaches, several groups initially were not able to produce similar results; their criticisms with our response have been published (28 -32).…”
Section: Table II the Higher Activity And Stability Of 5[k (Ch 2 N)prmentioning
confidence: 45%
“…More recently, it has been proposed that CDR3 synthetic peptides (28) or anti-CDR3 monoclonal antibodies (3) are able to inhibit the replication of HIV-1 after integration of the provirus. In our current model for the mechanism of action of V3 SPCs, the interaction between HIV envelope glycoproteins and the surface of CD4+ T lymphocytes and macrophages may involve the CDR3 region of CD4, and/or a distinct coreceptor (e.g., a cell surface protease), as previously postulated (6,26). The interaction between the potential coreceptors and the V3 loop could be inhibited by V3 SPCs.…”
Section: Inhibition Of Hiv-1 and Hiv-2 Infection Ofmentioning
confidence: 73%
“…With regard to function, CD26 is a binding or carrier protein for adenosine deaminase (12), an enzyme whose deficiency is strongly associated with severe combined immunodeficiency disease (31). Further, it has been suggested that CD26 is a putative coreceptor for human immunodeficiency virus (32 …”
Section: Importance Of Dppiv Enzyme Activity For the Enhancingmentioning
confidence: 99%